Chapter 3 Mucuna pruriens vs. Morbus Parkinson Making the case for medicinal supplements within Medicinal Agroecology - Fiebrig, Immo Norman (Taylor & Francis, 2023)
This current chapter reports an initially singular case of a PD patient in Germany who could not be treated with conventional PD medication and whose quality of life had deteriorated dramatically after diagnosis, including long episodes of psychoses. Following therapy with an Ayurvedic (botanical) preparation from the beans of Mucuna pruriens (MP) - the patient´s fate was improved substantially at the time. This compelling, and - rather by fortune - well-documented case was pivotal to spreading the experience with MP within the European network of PD patients, mostly by word of mouth. The PD patient community and neurologists were supported by available online information around the medicinal plant, MP, and the bean´s active components, as well as an initial clinical study followed by a second one in 2004. Based on this first evidence, some neurologists were willing to support their patients with MP-based complementary therapy. As far as the authors are aware, from approximately 1997 until to date such cases were treated predominantly in Germany, Switzerland, Austria and The Netherlands. Clinical experience is mainly based on the feedback from patients and volunteers pushing to understand the added value of MP and prompting the availability of a safe and effective natural medicinal product that can be prescribed to PD patients. Their findings constitute the basis of this chapter.